3D‐printed, bioactive ceramic scaffold with rhBMP‐2 in treating critical femoral bone defects in rabbits using the induced membrane technique. Issue 12 (24th February 2021) - Cho, Jae‐Woo; Kim, Beom‐Soo; Yeo, Do‐Hyun; Lim, Eic Ju; Sakong, Seungyeob; Lim, Junyoung; Park, SungNam; Jeong, Yong‐Hoon; Jung, Tae‐Gon; Choi, Hyuk; Oh, Chang‐Wug; Kim, Hak Jun; et al.
Abstract: Although autogenous bone grafts are an optimal filling material for the induced membrane technique, limited availability and complications at the harvest site have created a need for alternative graft materials. We aimed to investigate the effect of an rhBMP‐2‐coated, 3D‐printed, macro/microporous CaO–SiO2 –P2 O5 –B2 O3 bioactive ceramic scaffold in the treatment of critical femoral bone defects in rabbits using the induced membrane technique. A 15‐mm segmental bone defect was made in the metadiaphyseal area of the distal femur of 14 rabbits. The defect was filled with polymethylmethacrylate cement and stabilized with a 2.0 mm locking plate. After the membrane matured for 4 weeks, the scaffold was implanted in two randomized groups: Group A (3D‐printed bioceramic scaffold) and Group B (3D‐printed, bioceramic scaffold with rhBMP‐2). Eight weeks after implantation, the radiographic assessment showed that the healing rate of the defect was significantly higher in Group B (7/7, 100%) than in Group A (2/7, 29%). The mean volume of new bone formation around and inside the scaffold doubled in Group B compared to that in Group A. The mean static and dynamic stiffness were significantly higher in Group B. Histological examination revealed newly formed bone in both groups. Extensive cortical bone formation along the scaffold was found in Group B. Successful bone reconstruction in critical‐sized bone defects could be obtained using rhBMP‐2‐coated, 3D‐printed, macro/microporous bioactive ceramic scaffolds. This grafting material demonstrated potential as an alternative graft material in the induced membrane technique for reconstructing critical‐sized bone defects.